Velocity of detonation (VOD) measurement techniques - practical approach - Tete, Aruna Dhanraj; Deshmukh, A.Y.; Yerpude, R.R. (International Journal of Engineering and Technology, 2013)
Velocity of Detonation (VOD) is an important measure characteristics parameter of explosive material. The performance of explosive invariably depends on the velocity of detonation. The power/ strength of explosive to cause fragmentation of the solid structure determine the efficiency of the Blast performed. It is an established fact that measuring velocity of detonation gives a good indication of the strength and hence the performance of the explosive. In this survey various VOD measurement techniques such as electric, nonelectric and fibre optic have been discussed. To aid the discussion some commercially available VOD meter comparison are also presented. After review of the existing units available commercially and study of their respective merits and demerits, feature of an ideal system is proposed.